Organ recovery from deceased donors with prior COVID‐19: A case series. Issue 2 (1st December 2020) - Neidlinger, Nikole A.; Smith, Jeannina A.; D'Alessandro, Anthony M.; Roe, David; Taber, Tim E.; Pereira, Marcus R.; Friedman, Amy L.
Abstract: Although guidance documents have been published regarding organ donation from individuals with a prior history of COVID‐19 infection, no data exist regarding successful recovery and transplantation from deceased donors with a history of or positive testing suggesting a prior SARS‐CoV‐2 infection. Here, we report a case series of six deceased donors with a history of COVID‐19 from whom 13 organs were recovered and transplanted through several of the nation's organ procurement organizations (OPOs). In addition, at least two potential donors were authorized for donation but with no organs were successfully allocated and did not proceed to recovery. No transmission of SARS‐CoV‐2 was reported from the six donors to recipients, procurement teams, or hospital personnel. Although more studies are needed, organ donation from deceased donors who have recovered from COVID‐19 should be considered.